Hypercalcemia and Neurological Symptoms: A Rare Presentation of Hyperfunctioning Parathyroid Adenoma in an Adolescent - Calcaterra, Valeria; Pelizzo, Gloria; Pipolo, Andreana; Montecamozzo, Giulio; Fabiano, Valentina; Grazi, Roberta; Carlucci, Patrizia; Zuccotti, Gianvincenzo (Frontiers in Surgery, 2022)
Neuropsychiatric symptoms are rarely described as a manifestation of hyperparathyroidism, especially in children. We describe the case of an adolescent with hypercalcemia related to and hyperfunctioning parathyroid adenoma presenting with acute neuropsychiatric symptoms. A 14-year-old-girl presented into the Emergency Service Department because of an acute onset of marked asthenia, muscle weakness with difficulty in walking, and altered mental status, which included nonsensical speech. No other neurological signs were present. Abdominal, cardiac, and thoracic examination were unremarkable. There was no recent history of trauma or infection. Family history was negative for neurologic disorders. Her past medical history was unremarkable. A head CT scan showed negative results. The laboratory work-up showed elevated levels of calcium level (14.35 mg/dl; nv 9–11 mg/dl), parathyroid hormone (PTH; 184 pg/ml; nv 3.5–36.8 pg/ml), and creatinine (1.23 mg/dl; nv 0.45–0.75 mg/dl). Sodium, potassium, chloride, thyroid function, glycemia, and insulin values were normal. Neck ultrasonography showed a solid, oval, capsulated, hypoechoic neoformation, with discrete vascularization localized to the inferior pole of the right thyroid lobe, referring to parathyroid tissue. Scintigraphy revealed a hyperfunctioning parathyroid tissue at the inferior pole of the right thyroid lobe. Massive intravenous hydration and diuretic therapy were started. The signs and symptoms of hypercalcemia improved after the initiation of therapy. The patient was submitted to right cervicotomy and muscle sparing for the removal of the adenoma of the right superior parathyroid gland. After surgery, a decrease in PTH levels (<4 pg/ml) and calcium levels (9.1 mg/dl) was recorded. During follow-up, calcium values remained stable; a progressive normalization of PTH was obtained. The oral calcium therapy was suspended after 3 months from surgery. No neuropsychiatric symptoms recurred. An evaluation of the serum calcium level is mandatory in children and adolescents with unexplained neurological signs or symptoms, and a check for hyperparathyroidism should be considered.